Surgical treatment of isolated tricuspid valve infective endocarditis: 25-year results from a multicenter registry. (1st October 2019) - Di Mauro, Michele; Foschi, Massimiliano; Dato, Guglielmo Mario Actis; Centofanti, Paolo; Barili, Fabio; Corte, Alessandro Della; Ratta, Ester Della; Cugola, Diego; Galletti, Lorenzo; Santini, Francesco; Salsano, Antonio; Rinaldi, Mauro; et al.
Abstract: Background: To assess early and late mortality in patients with isolated acute tricuspid valve infective endocarditis (TVIE) using data from a multicenter registry. Methods: From 1983 to 2018, isolated acute TVIE was surgically treated in 157 (3.8%) patients [mean age 47 ± 16 years (range 15–86 years), 25% females]. Of these, 142 (90%) had native tricuspid regurgitation, 7 (5%) native tricuspid valve (TV) steno-regurgitation, and 8 (5%) prosthetic TVIE. Intravenous drug use (IVDU) was recorded in 38% of patients, infection involved cardiac implantable electronic device leads in 21%, and vascular catheters for dialysis in 1%; in the remaining cases, the cause was unknown. The primary endpoint was in-hospital outcome, long-term freedom from recurrence and overall survival. Results: Overall, 77 (49%) patients underwent TV repair, 72 (46%) TV replacement, and 8 (5%) prosthetic TV replacement. Early mortality was 11% (n = 17). Expected early mortality according to EndoSCORE was 12%, with age (odds ratio 1.06) and redo (odds ratio 6.64) as risk factors. Late deaths occurred in 31 patients and TVIE recurrences in 4. Survival rates at 10, 20, and 25 years were 66%, 60%, and 44%, respectively. Risk factors were age [hazard ratio (HR) 1.06], mycotic TVIE (HR 4.2), IVDU (HR 4.90), infected prosthesis replacement (HR 4.4), and presence of cardiac implantable electronic device leads (HR 3.0). No significant difference was found in valve repair vs. replacement and in IVDUs vs. non-IVDUs. Conclusions: Patients with isolated acute TVIE undergoing surgical treatment show acceptable early and late outcomes. TVIE recurrence was low, and repair of the affected valve does not seem to confer any advantage either at early or long term up to 25 years. Highlights: Patients with TVIE are younger with higher prevalence of IVDU. In TVIE, Staphylococcus aureus is the most common pathogen. Age, fungal TVIE, IVDU, redo operation and leads are risk factors TVIE undergoing surgical treatment show acceptable early and late outcomes.